Instilling religious values in young learners: A narrative exploration of teachers’ roles and realities - Tohirin; Mustafa, Fitri; Emha, Rifa’atul Mahmudah; Jarudin; Afiyah, Nur; Ulfah, Fitria Nabila; Solahudin, Aah; Irma, Ade; Kirom, Tubagus Tsalasna Arzaqul; Mawar, Agus; Aljihaad, Muhammad Muslim; Sari, Reny Puspita; et al. (Research Journal in Advanced Humanities, 2025)
This study investigated the strategies and challenges encountered by public elementary school teachers in Kedurang District, South Bengkulu Province, in their efforts to instill Islamic religious values in students. Employing a narrative inquiry approach, the research explored the lived experiences of six teachers through interviews, observations, and documentation. The findings revealed that teachers employed a range of strategies, including routine-based habituation (e.g., congregational prayers and moral reminders), role modeling, the use of visual media, and collaborative activities with parents and communities. Programs such as Jumat Berkah, Pesantren Kilat, and Ramadan journals serve as both instructional and character-building tools, embedding religious values into daily student experiences. Despite these efforts, teachers encountered persistent challenges, notably student discipline issues, varied engagement levels, and classroom management difficulties, often linked to students’ diverse backgrounds and learning preferences. The study underscores the pivotal role of teachers as moral agents and emphasizes the need for adaptive, emotionally engaging, and collaborative pedagogical approaches. Findings contribute to value-based education literature by highlighting context-specific strategies in secular public schools and recommending ongoing teacher development and stronger school-parent partnerships for sustained religious character formation.